Edukasi Kesehatan dan Skrining Glukosa Darah sebagai Upaya Deteksi Dini Diabetes Melitus pada Masyarakat di Jungsereh Garut - Meti Rizki Utari; Mamay Mamay; Muhammad Hadi Sulhan; Sugiah Sugiah; Lia Maratiningsih; Gina Nafsa Mutmaina; Astari Nurisani; Yogi Rahman Nugraha; Firman Muharam (Jurnal Pengabdian Bidang Kesehatan, 2026)
Abstract: Diabetes mellitus is a metabolic disorder characterized by elevated blood glucose levels and remains a growing public health concern. Limited public awareness regarding routine health examinations contributes to the late detection of diabetes cases. This community service activity aimed to evaluate blood glucose profiles among residents in the Jungsereh Garut area as an effort for early screening of diabetes mellitus risk. Blood glucose measurements were conducted using a glucometer through capillary blood sampling among participants who attended the health screening program. A total of 24 participants aged 21–80 years were involved in the activity. Data were analyzed descriptively and classified into normal, prediabetes, and high blood glucose categories. The results showed that 8 participants (33.3%) had normal blood glucose levels, 12 participants (50%) were categorized as prediabetic, and 4 participants (16.7%) had high blood glucose levels. The highest glucose level was 152 mg/dL, while the lowest was 85 mg/dL, with an average level of 108 mg/dL. These findings indicate that most participants were at the prediabetes stage, highlighting the importance of continuous health education and routine screening programs to prevent diabetes mellitus development in the community.